Current state and use of the steppe zone transboundary rivers’ water resources - Zhanna T. Sivokhip; Vladimir M. Pavleychik (Водное хозяйство России: проблемы, технологии, управление)
Th e problems of guaranteed supply of water resources are particularly acute in regions with unstable moisture, including those located within the steppe zone. Th e work assesses the current state and use of water resources in the transboundary basins of the Ural and Irtysh rivers within the steppe zone. Th e spatial/temporal heterogeneity of the river runoff has been noted, due to the diff erentiated distribution of atmospheric precipitation and local physical and geographical conditions.